Induction of tetraploids in Paper Mulberry (Broussonetia papyrifera (L.) L’Hér. ex Vent.) by colchicine - Jiana Lin; Bingnan Zhang; Jintuo Zou; Zhen Luo; Hao Yang; Peng Zhou; Xiaoyang Chen; Wei Zhou (BMC Plant Biology, 2023)
Abstract Background Broussonetia papyrifera (L.) L’Hér. ex Vent. has the characteristics of strong stress resistance, high crude protein content, and pruning tolerance. It is an ecological, economic, and medicinal plant. Polyploid plants usually perform better than their corresponding diploid plants in terms of nutrients, active substances, and stress resistance. Results In this study, the leaves, calli, and seeds of diploid B. papyrifera were used for tetraploid induction by colchicine. The induction effect of colchicine on B. papyrifera was summarized through the early morphology, chromosome count and flow cytometry. It was concluded that the best induction effect (18.6%) was obtained when the leaves of B. papyrifera were treated in liquid MS (Murashige and Skoog) medium containing 450 mg·L-1 colchicine for 3 d. The comparative analysis of the growth characteristics of diploid and tetraploid B. papyrifera showed that tetraploid B. papyrifera has larger ground diameter, larger stomata, thicker palisade tissue and thicker sponge tissue than diploid B. papyrifera. In addition, the measurement of photosynthetic features also showed that tetraploids had higher chlorophyll content and higher photosynthetic rates. Conclusion This study showed that tetraploid B. papyrifera could be obtained by treating leaves, callus and seeds with liquid and solid colchicine, but the induction efficiency was different. Moreover, there were differences in stomata, leaf cell structure and photosynthetic features between tetraploid B. papyrifera and its corresponding diploid. The induced tetraploid B. papyrifera can provide a technical basis and breeding material for the creation of B. papyrifera germplasm resources in the future.